2001
DOI: 10.1590/s0103-50532001000100008
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasonic baths for analytical applications: a new approach for optimisation conditions

Abstract: Com o emprego de um método simples e rápido, são propostas algumas condições de otimização para a obtenção de máxima intensidade de cavitação em banhos de ultra-som. Os parâmetros estudados foram: volume de água dentro do banho, temperatura, concentração de detergente, posição vertical e horizontal dos tubos no banho, número de tubos dentro do banho, tempo de sonicação e substituição da água do banho. Os resultados obtidos para os banhos de ultra-som estudados (Neytech e Cole-Parmer) permitiram estabelecer as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 22 publications
2
40
0
4
Order By: Relevance
“…Vessels were kept in the central position of the bath for all samples and water was periodically changed to keep the temperature around 25-30 °C. These conditions are compatible with those established by Nascentes et al 27 As expected, sulfur and selenium are mainly contained in the protein fraction. Previous study has shown that selenium is covalently bond to proteins by methionine and cysteine amino acids.…”
Section: Fractionation Of Barium Based On Chemical Compositionsupporting
confidence: 92%
“…Vessels were kept in the central position of the bath for all samples and water was periodically changed to keep the temperature around 25-30 °C. These conditions are compatible with those established by Nascentes et al 27 As expected, sulfur and selenium are mainly contained in the protein fraction. Previous study has shown that selenium is covalently bond to proteins by methionine and cysteine amino acids.…”
Section: Fractionation Of Barium Based On Chemical Compositionsupporting
confidence: 92%
“…The reaction vial was placed in the maximum energy area in the cleaner. 44 Water was added or removed in order to control the bath temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Soc. incidence and maintaining the level of the solution in the sonoreactor equal to the water level in the ultrasonic bath. 10 The temperature during sonication was maintained at 15±1 o C with a Tecnal TE184 thermostatic bath (Piracicaba, Brazil).…”
Section: Apparatusmentioning
confidence: 99%